KERANGKA KERJA ERM DAN PENERAPANNYA PADA BISNIS WARALABA FRANCHISE TEA BREAK DI SIDOARJO - Balqis Milad Ar-Rizqy; Adilian Rifqi; Elsi Mersilia Hanesti (LPPM STIE PERTIBA Pangkalpinang, 2023)
Every business or company has risks that are likely to occur, meaning that every business/company that is carried out will be inversely proportional to the risks that follow. Entrepreneurs make risks that are likely to occur in the future used as the main reference/goal by staying away from risks and managing risks. The task of the company/business is to deal with risks that will occur, namely, investors as avoiding risks and management as risk managers, namely reducing the possibility of risks occurring. This study examines the application of ERM in the Tea Break franchise business. The purpose of this study is to find out the various risks that exist in the tea break franchise business and to find out how the ERM framework is applied to the tea break franchise business. The type of research used to conduct this research is using a qualitative descriptive analysis approach by collecting data by means of field studies, namely by means of interviews, observation, and documentation. Sources of data used in this research are primary data and secondary data. Primary data using observation and interview methods. Secondary data usually comes from library research by collecting, reading, and understanding theories from books, journals, magazines, or data from relevant internet theories.